INFLUENCE OF PLANT DENSITY ON CELERY ROOT PRODUCTIVITY - Матвиенко, Андрей; Бобось, Ирина (SWorldJournal, 2020)
Due to the valuable qualities, the demand for celery is increasing and the acreage in Ukraine is increasing, the seedlings of which began to grow in a cassette manner. Among the insufficiently studied technological elements in the Kiev region is optimiza